2023
DOI: 10.1200/jco.2023.41.16_suppl.e18016
|View full text |Cite
|
Sign up to set email alerts
|

Chronotherapy in head and neck cancer (HNC): A systematic review.

Abstract: e18016 Background: Chronotherapy in cancer is optimizing the administration time of anti-cancer treatment according to circadian rhythm and cellular phase to improve the efficacy against tumor cells while decreasing side effects on normal cells. Several randomized controlled trials (RCT) evaluated chronotherapy of chemotherapy (chrono-chemotherapy: time-specific infusions) and/or radiotherapy (chrono-radiotherapy: morning radiotherapy) in various cancers and reported improved treatment efficacy and reduced to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a different prostate cancer study, patients that received photo beam radiotherapy between 0830 h and 1030 h had fewer lower urinary tract symptoms and double the quality-of-life score compared to patients that received evening doses [ 59 ]. A recent review consisting of nine chrono-radiotherapy studies involving individuals with head and neck cancer reported that chronomodulating treatment was associated with reduced radiotherapy toxicity, despite no differences in treatment response observed across four of the studies [ 64 ]. Rates of treatment-induced oral mucositis were also analyzed, and whereas no differences were reported between groups in overall prevalence, the latency at which mucositis developed was significantly increased in the group receiving afternoon radiotherapy [ 65 ].…”
Section: Chrono-radiotherapy For Solid Tumor Treatmentmentioning
confidence: 99%
“…In a different prostate cancer study, patients that received photo beam radiotherapy between 0830 h and 1030 h had fewer lower urinary tract symptoms and double the quality-of-life score compared to patients that received evening doses [ 59 ]. A recent review consisting of nine chrono-radiotherapy studies involving individuals with head and neck cancer reported that chronomodulating treatment was associated with reduced radiotherapy toxicity, despite no differences in treatment response observed across four of the studies [ 64 ]. Rates of treatment-induced oral mucositis were also analyzed, and whereas no differences were reported between groups in overall prevalence, the latency at which mucositis developed was significantly increased in the group receiving afternoon radiotherapy [ 65 ].…”
Section: Chrono-radiotherapy For Solid Tumor Treatmentmentioning
confidence: 99%